A new species of the genus Olopachys (Mesostigmata: Pachylaelapidae) from Mazandaran Province, Iran, with a review of the Iranian species. Issue 8 (17th November 2019) - Moghimi, Fatemeh; Ahadiyat, Ali; Kiadaliri, Hadi; Karaca, Mehmet
ABSTRACT: A new species of Olopachys Berlese, Olopachys ( Olopachys ) magnoexudatus sp. nov ., is described herein, based on female specimens collected from soil and litter in the natural forests of Behshahr, Mazandaran Province, Iran. All previous records of Olopachys species in Iran are reviewed and discussed, and an identification key to the five Iranian species is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:C03735E5-D41D-4DBF-B879-243E6E517456